Evaluasi Atas Pengakuan Pendapatan Pada Perusahaan Jasa Konstruksi Kaitannya Terhadap Laporan Laba Rugi Perusahaan - Hasibuan, David HM; Marpaung, Annaria Magdalena; Gunawan, Yosep (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2011)
The researchâs goal is to evaluate income acknowledgement at construction service company that make work contract on construction with work giver. The evaluation is intended to find out the correlation of income acknowledgement conducted by PT. Nusa Sukses Jaya, towards the companyâs profit and loss accounting. The result of the research shows that PT. Nusa Sukses Jaya has not carried out income acknowledgement and responsibility yet well enough. By using percentage method, responsibility accomplishment has not been calculated yet in a reliable manner with the result that gross profit canât be found out at the accomplishment phase. From the evaluation result done by the author at PT. Nusa Sukses Jaya, it can be concluded that income of construction service company is in the form of project income. That income was acknowledged by the company by utilizing finished contract method and accomplishment percentage method. So was responsibility accomplishment. Accounting policy determined for profit and has accounting by PT. Nusa Sekses Jaya has not been in mutual accord yet with PSAK No.1 concerning Finance Accounting Statement. No cash flow accounting and equity change on the annual finance accounting of PT. Nusa Sukses Jaya, particularly in the year 2008.